Factors associated with health‐related quality of life in heart failure in 23 000 patients from 40 countries: results of the G‐CHF research programme. (15th June 2022) - Johansson, Isabelle; Balasubramanian, Kumar; Bangdiwala, Shrikant; Mielniczuk, Lisa; Hage, Camilla; Sharma, Sanjib Kumar; Branch, Kelley; Zhu, Jun; Kragholm, Kristian; Sliwa, Karen; Alla, Francois; Yonga, Gerald; et al.
Abstract: Aims: To examine clinical and social correlates of health‐related quality of life (HRQL) in patients with heart failure (HF) from high‐ (HIC), upper middle‐ (UMIC), lower middle‐ (LMIC) and low‐income (LIC) countries. Methods and results: Between 2017 and 2020, 23 292 patients with HF (32% inpatients, 61% men) from 40 countries were enrolled in the Global Congestive Heart Failure study. HRQL was recorded at baseline using the Kansas City Cardiomyopathy Questionnaire (KCCQ)‐12. In a cross‐sectional analysis, we compared age‐ and sex‐adjusted mean KCCQ‐12 summary scores (SS: 0–100, higher = better) between patients from different country income levels. We used multivariable linear regression examining correlations (estimated coefficients) of KCCQ‐12‐SS with sociodemographic, comorbidity, treatment and symptom covariates. The adjusted model (37 covariates) was informed by univariable findings, clinical importance and backward selection. Mean age was 63 years and 40% of patients were in New York Heart Association (NYHA) class III–IV. Average HRQL was 55 SD 27. It was 62.5 (95% confidence interval [CI] 62.0–63.1) in HIC, 56.8 (56.1–57.4) in UMIC, 48.6 (48.0–49.3) in LMIC, and 38.5 (37.3–39.7) in LICs ( p  < 0.0001). Strong correlates (estimated coefficient [95% CI]) of KCCQ‐12‐SS were NYHA class III versus class I/II (−12.1 [−12.8 to −11.4] and class IV versus class I/II (−16.5 [−17.7 to −15.3]), effort dyspnoea (−9.5 [−10.2 to −8.8]) and living in LIC versus HIC (−5.8 [−7.1 to −4.4]). Symptoms explained most of the KCCQ‐12‐SS variability (partial R 2  = 0.32 of total adjusted R 2  = 0.51), followed by sociodemographic factors (R 2  = 0.12). Results were consistent in populations across income levels. Conclusion: The most important correlates of HRQL in HF patients relate to HF symptom severity, irrespective of country income level. Abstract : Signs and symptoms of congestion were the strongest independent correlates of health‐related quality of life (HRQL) and explained most of the variability in the Kansas City Cardiomyopathy Questionnaire‐12 summary score (KCCQ‐12‐SS). This was consistent across country income groups and most pronounced in low‐income countries (LICs). Improved symptom control may have a big impact on HRQL, especially in LICs. Adj, adjusted; CI, confidence interval; HF, heart failure; HIC, high‐income country; LMIC, lower middle‐income country; NYHA, New York Heart Association; UMIC, upper middle‐income country. *Estimates (estimated coefficients) after multivariable adjustment. Estimates indicate the change in mean KCCQ‐12‐SS by each unit change in the covariate. KCCQ‐12‐SS range (0 to 100, higher score = better HRQL). **Partial R 2 ‐values represent contribution of groups of covariates when added as follows: (i) sociodemographic characteristics, (ii) comorbidities, (iii) treatments for HF, and (iv) signs and symptoms of congestion.